RELASI SUAMI-ISTERI DAN PENGARUHNYA DALAM PROSES PEMBENTUKAN KEPRIBADIAN DAN IMAN ANAK: : TINJAUAN PSIKOLOGI - Seralarat, Kornelis (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2016)
The growth and development of children occurs within a family. The quality of children's personality development and faith is highly dependent on the quality of their parents and children relationships in a family. Relationship between parents and children is also determined by the quality of the relationship of husband and wife. Thus, the quality of husband and wife relationship and parenting style influence the developmental maturity of the personality and the faith of their children. The purpose of this paper is to explain the quality of husband and wife relationships and parenting style in a nuclear family and its impact on the process of personality formation and faith of the children from the perspective of psychology.